Age-Dependent Constraints of Sex Allocation in a Parasitoid Wasp - Takatoshi Ueno (Psyche: A Journal of Entomology)
The offspring sex ratios of parasitoid wasps often depend on the age of ovipositing females. Physiological constraints such as sperm depletion and senescence are a likely cause. Also, maternal control in response to female age may be an alternative explanation. Here valvifer or abdominal tip movements were used to assess whether age-dependent sex ratio was due to physiological constraints or maternal control with an ichneumonid wasp, Pimpla nipponica; the offspring sex ratio at the time of wasp emergence was compared with the sex ratio predicted from abdominal tip movements. When the female was relatively young, there was little difference between the sex ratios examined. However, as the age of the females increased, the realized offspring sex ratio at wasp emergence was more male-biased than the sex ratio predicted at the time of oviposition. Thus, there was an inconsistency between the sex ratios. Curiously, the predictions of continuous movements for male egg deposition were always perfect, regardless of maternal age; fertilization control failure was detected when the females had decided to lay female eggs. Thus, physiological constraints are a likely explanation for the inconsistency in relation to female age for P. nipponica.